Recombinant Tissue Factor Pathway Inhibitor Prevents Lipopolysaccharide-induced Systemic Hypotension in Rats by Inhibiting Excessive Production of Nitric Oxide - Enkhbaatar, Perenlei; Okajima, Kenji; Uchiba, Mitsuhiro; Isobe, Hirotaka; Okabe, Hiroaki (Thrombosis and Haemostasis, 2001)
Excessive production of nitric oxide (NO) by the inducible form of NO synthase (iNOS) plays a key role in the development of endotoxin shock. Tumor necrosis factor-α (TNF-α) induces iNOS, thereby contributing to the development of shock. We recently reported that recombinant tissue factor pathway inhibitor (r-TFPI), an important inhibitor of the extrinsic pathway of the coagulation system, inhibits TNF-α production by monocytes. In this study, we investigated whether r-TFPI could ameliorate hypotension by inhibiting excessive production of NO in rats given lipopolysaccharide (LPS). Pretreatment of animals with r-TFPI prevented LPS-induced hypotension. Recombinant TFPI significantly inhibited the increases in both the plasma levels of NO2-/NO3- and lung iNOS activity 3 h after LPS administration. Expression of iNOS mRNA in the lung was also inhibited by intravenous administration of r-TFPI. However, neither DX-9065a, a selective inhibitor of factor Xa, nor an inactive derivative of factor VIIa (DEGR-F.VIIa) that selectively inhibits factor VIIa activity, had any effect on LPS-induced hypotension despite their potent anticoagulant effects. Moreover, neither the plasma levels of NO2-/NO3- nor lung iNOS activity were affected by administration of DX-9065a and DEGR-F.VIIa. These results suggested that r-TFPI ameliorates LPS-induced hypotension by reducing excessive production of NO in rats given LPS and this effect was not attributable to its anticoagulant effects, but to the inhibition of TNF-α production.
Keywords: Recombinant tissue factor pathway inhibitor; nitric oxide; tumor necrosis factor-α; hypotension; inducible nitric oxide synthase